Determination of blood lactate training zone boundaries with rating of perceived exertion in runners - Dantas, J. L.; Doria, C.; Rossi, H.; Rosa, G.; Pietrangelo, T.; Fanò-Illic, G.; Nakamura, F. Y. (The Journal of Strength and Conditioning Research, 2015)
This study aimed to determine the rating of perceived exertion (RPE) values corresponding to the blood lactate concentration (BLC) training zone boundaries (2 and 4 mmol/L) in moderately trained runners using the Borg CR-10 scale. Moderately trained runners (n = 95) performed a submaximal incremental test on a treadmill, recording BLC and RPE at every stage. Simple linear regression analysis was used to determine the RPE values corresponding to the BLC training zone boundaries, which revealed that RPE was significantly and strongly correlated with BLC (r = 0.821, p < 0.001, R2 = 0.675, adjusted R2 = 0.674, standard error of estimate = 1.18). The prediction equation (RPE = 1.092 × BLC + 2.143) was obtained, and RPE values at the BLC training zone boundaries of 2 and 4 mmol/L were calculated as 4.3 (95% confidence interval [CI], 3.9-4.7) and 6.5 (95% CI, 6.0-7.1), respectively. In conclusion, the RPE values at the BLC training zone boundaries of 2 mmol/L (4.3) and 4 mmol/L (6.5) were adequately predicted. Rating of perceived exertion (4.3 and 6.5) can be used as an affordable tool for controlling intensity to maintain the athletes in prescribed zones during training sessions.